Case Report: True Motor Recovery of Upper Limb Beyond 5 Years Post-stroke - Ciceron, Carine; Sappey-Marinier, Dominique; Riffo, Paola; Bellaiche, Soline; Kocevar, Gabriel; Hannoun, Salem; Stamile, Claudio; Redoute, Jérôme; Cotton, Francois; Revol, Patrice; Andre-Obadia, Nathalie; Luaute, Jacques; et al. (Frontiers in Neurology, 2022)
Most of motor recovery usually occurs within the first three months after stroke. Herein is reported a remarkable late recovery of the right upper-limb motor function after a left middle cerebral artery stroke. This recovery happened progressively, from two to twelve years post-stroke onset, and along a proximo-distal gradient, including dissociated finger movements after five years. Standardised clinical assessment and quantified analysis of the reach-to-grasp movement were repeated over time to characterise the recovery. Twelve years after stroke onset, diffusion tensor imaging (DTI), functional magnetic resonance imaging (fMRI), and transcranial magnetic stimulation (TMS) analyses of the corticospinal tracts were carried out to investigate the plasticity mechanisms and efferent pathways underlying motor control of the paretic hand. Clinical evaluations and quantified movement analysis argue for a true neurological recovery rather than a compensation mechanism. DTI showed a significant decrease of fractional anisotropy, associated with a severe atrophy, only in the upper part of the left corticospinal tract (CST), suggesting an alteration of the CST at the level of the infarction that is not propagated downstream. The finger opposition movement of the right paretic hand was associated with fMRI activations of a broad network including predominantly the contralateral sensorimotor areas. Motor evoked potentials were normal and the selective stimulation of the right hemisphere did not elicit any response of the ipsilateral upper limb. These findings support the idea that the motor control of the paretic hand is mediated mainly by the contralateral sensorimotor cortex and the corresponding CST, but also by a plasticity of motor-related areas in both hemispheres. To our knowledge, this is the first report of a high quality upper-limb recovery occurring more than two years after stroke with a genuine insight of brain plasticity mechanisms.